Vulnerable to the virus: Globally-oriented manufacturing firms at risk from the spread of COVID-19 - Karl Robert L. Jandoc; Adrian Mendoza; Stella Luz Quimbo (University of the Philippines, School of Economics (UPSE), 2020)
We use a unique Philippine firm-level database consisting of trade transactions data merged with firm surveys of manufacturing establishments covering the period from 2013 to 2019 to examine which exporting and importing firms are potentially vulnerable to the economic slowdown brought about by the spread of COVID-19. We find that the exposure of Philippine trade to the COVID-19 affected countries is substantial, accounting for more than half of the value of both exports and imports. Those that stand to lose the most are firms connected to the global value chains that simultaneously export and import. Around 370,000 workers from these firms are at risk. While large firms are able to withstand, to some extent,the COVID-19 shock, SMEs do not have such capability. We find that the profile of these SMEs is substantially different than that of the larger firms in terms of product composition. These SMEs export food and food products which are highly perishable and more sensitive even to short-term vicissitudes in global demand. Given these, we estimate the subsidy needed to support both SMEs and large firms. For SMEs, we compute the subsidy to be Php9.4 billion pesos for 2020. The amount of subsidy increases to Php33.2 billion if large firms were also subsidized for their losses. Identifying the specific mechanism by which such subsidies will be provided to firms of various sizes (e.g. SMEs vs large) requires further study.
Keywords: O14; L11; H25; 330; COVID-19; Philippine Firms; Stimulus Package